Efektivitas Penerapan Strategi Pembelajaran Aktif pada Mata Pelajaran Pendidikan Agama Islam dalam Meningkatkan Motivasi Belajar Siswa Kelas X di SMKS YPKP TIK Sentani - Maharani Intasn Sya’ada Mahifa; Talabudin Umkabu; Sigit Purwaka (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This study aims to determine the effectiveness of active learning strategies in Islamic Religious Education subjects in improving the learning motivation of tenth-grade students at SMKS YPKP TIK Sentani. This research is motivated by the low level of student involvement and learning motivation in the learning process, which is still dominated by lecture methods, causing students to become passive, less confident, and less enthusiastic in participating in lessons. Active learning strategies were chosen because they are able to directly involve students through discussions, question-and-answer activities, group work, and various other student-centered learning activities.This study used a qualitative research method with a descriptive approach. The research was conducted at SMKS YPKP TIK Sentani, Jayapura Regency. Data collection techniques included observation, interviews, and documentation. A pedagogical approach was used to analyze the learning process and the effectiveness of active learning strategies in improving students’ learning motivation in Islamic Religious Education subjects.The results showed that the implementation of active learning strategies was effective in improving students’ motivation and learning outcomes. Students became more active in asking questions, participating in discussions, and expressing opinions, making the learning atmosphere more interactive and enjoyable. In addition, active learning strategies also had a positive impact on changes in students’ learning behavior, such as increased self-confidence, discipline, responsibility, and participation in the learning process. Students’ learning motivation increased due to intrinsic factors, such as the desire to understand the material and achieve academic success, as well as extrinsic factors, including interesting teaching methods, teacher support, the use of learning media, and a conducive classroom environment. Therefore, active learning strategies can be used as an effective learning alternative to improve students’ motivation, participation, and learning outcomes in Islamic Religious Education subjects.